Hubungan Pola Makan terhadap Kadar Gula Darah pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Baki Sukoharjo - Budi Prasetyo Nugroho; Witriyani Witriyani; Ady Irawan AM (Universitas Muhammadiyah Klaten, 2026)
Background: Type 2 diabetes mellitus is a chronic condition characterized by elevated blood glucose levels due to metabolic disorders. Dietary management is an essential strategy to control blood glucose levels. However, many patients fail to adhere to healthy eating principles (type, timing, and amount), potentially worsening their condition. This study aims to determine the relationship between dietary patterns and blood glucose control among patients with type 2 diabetes mellitus. Methods: This study used a quantitative correlational design with a cross-sectional approach. A total of 103 respondents with type 2 diabetes mellitus were selected through purposive sampling at Baki Health Center, Sukoharjo. Data were collected using a Food Frequency Questionnaire (FFQ) and random blood glucose testing using a glucometer. Data analysis was performed using the chi-square test with a significance level of p < 0.05. Results: The findings showed a significant association between dietary patterns and blood glucose control, with an exact p-value of 0.002. Respondents with good dietary patterns were more likely to have controlled blood glucose levels than those with poor dietary patterns. Conclusion: There is a significant correlation between dietary patterns and blood glucose control among patients with type 2 diabetes mellitus. Continuous education on healthy dietary practices is essential to support preventive and curative diabetes management. Healthcare professionals have an important role in assisting patients to consistently adopt appropriate dietary habits to reduce the risk of long-term complications.